2018
DOI: 10.1038/s41416-018-0283-7
|View full text |Cite
|
Sign up to set email alerts
|

Mice deficient in the mitochondrial branched-chain aminotransferase (BCATm) respond with delayed tumour growth to a challenge with EL-4 lymphoma

Abstract: Background The mitochondrial branched-chain aminotransferase (BCATm) is a recently discovered cancer marker with a poorly defined role in tumour progression. Methods To understand how a loss of function of BCATm affects cancer, the global knockout mouse BCATmKO was challenged with EL-4 lymphoma under different diet compositions with varying amounts of branched-chain amino acids (BCAAs). Next, the growth and metabolism of EL-4 cells were studied in the presence of differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 50 publications
0
11
0
Order By: Relevance
“…For example, Ananieva et al. showed that BCATm knock-out mice, which display high levels of circulating BCAAs, have a reduced tumour growth; of note, in their animals, mTORC1 was not upregulated [ 82 ]. On the contrary, elevated concentrations of BCAAs have led to increased tumour growth when associated with upregulation of mTORC1 activity [ 83 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, Ananieva et al. showed that BCATm knock-out mice, which display high levels of circulating BCAAs, have a reduced tumour growth; of note, in their animals, mTORC1 was not upregulated [ 82 ]. On the contrary, elevated concentrations of BCAAs have led to increased tumour growth when associated with upregulation of mTORC1 activity [ 83 ].…”
Section: Discussionmentioning
confidence: 99%
“…1 ). However, incubation with three-fold amounts of EAAs 26 had no effect on the ACE2 or p-EIF2A expression levels (Supplementary Fig. 2 ), indicating that ACE2 responded particularly to amino acid deficiency.…”
Section: Resultsmentioning
confidence: 97%
“… Comparison of leucine catabolism in immune and cancer cells . The two reactions in leucine catabolism, transamination, and irreversible oxidation, were compared as a percent distribution in T cells, microphages, and cancer cells based on unpublished and published reports [ 54 , 69 , 70 ] . co-Stim: anti-CD3 and anti-CD28 co-stimulated mouse CD4 + T cells; EL4: murine T-cell lymphoma; LPS: lipopolysaccharide stimulated Raw 264.7 macrophages; SCLC: murine small-cell lung cancer; TCR, anti-CD3 stimulated CD4 + mouse T cells; un-stim: unstimulated murine CD4 + T cells or Raw 264.7 macrophages.…”
Section: Transamination Is the Most Important Step Of Bcaa Degradatio...mentioning
confidence: 99%
“…Some published data and ongoing research suggest that the BCAT isoenzymes may exert immunosuppressive functions in the TME [ 12 14 , 48 , 54 , 70 ] . As described in Ananieva’s reports, the BCAT isoenzymes might be a part of a critical resistance mechanism that involves a BCAT-dependent negative feedback regulation of mTORC1 signaling during T-cell activation and may serve as an essential metabolic checkpoint of T-cell function in TME [ 48 , 54 ] .…”
Section: Bcatc and Bcatm Are New Candidates For Immune Metabolic Chec...mentioning
confidence: 99%
See 1 more Smart Citation